Development of a Novel Risk Prediction Model for Sudden Cardiac Death in Childhood Hypertrophic Cardiomyopathy (HCM Risk-Kids) - Norrish, Gabrielle; Ding, Tao; Field, Ella; Ziólkowska, Lidia; Olivotto, Iacopo; Limongelli, Giuseppe; Anastasakis, Aristides; Weintraub, Robert; Biagini, Elena; Ragni, Luca; Prendiville, Terence; Duignan, Sophie; et al. (JAMA cardiology, 2019)
IMPORTANCE: Sudden cardiac death (SCD) is the most common mode of death in childhood hypertrophic cardiomyopathy (HCM), but there is no validated algorithm to identify those at highest risk. OBJECTIVE: To develop and validate an SCD risk prediction model that provides individualized risk estimates. DESIGN, SETTING, AND PARTICIPANTS: A prognostic model was developed from a retrospective, multicenter, longitudinal cohort study of 1024 consecutively evaluated patients aged 16 years or younger with HCM. The study was conducted from January 1, 1970, to December 31, 2017. EXPOSURES: The model was developed using preselected predictor variables (unexplained syncope, maximal left-ventricular wall thickness, left atrial diameter, left-ventricular outflow tract gradient, and nonsustained ventricular tachycardia) identified from the literature and internally validated using bootstrapping. MAIN OUTCOMES AND MEASURES: A composite outcome of SCD or an equivalent event (aborted cardiac arrest, appropriate implantable cardioverter defibrillator therapy, or sustained ventricular tachycardia associated with hemodynamic compromise). RESULTS: Of the 1024 patients included in the study, 699 were boys (68.3%); mean (interquartile range [IQR]) age was 11 (7-14) years. Over a median follow-up of 5.3 years (IQR, 2.6-8.3; total patient years, 5984), 89 patients (8.7%) died suddenly or had an equivalent event (annual event rate, 1.49; 95% CI, 1.15-1.92). The pediatric model was developed using preselected variables to predict the risk of SCD. The model's ability to predict risk at 5 years was validated; the C statistic was 0.69 (95% CI, 0.66-0.72), and the calibration slope was 0.98 (95% CI, 0.59-1.38). For every 10 implantable cardioverter defibrillators implanted in patients with 6% or more of a 5-year SCD risk, 1 patient may potentially be saved from SCD at 5 years. CONCLUSIONS AND RELEVANCE: This new, validated risk stratification model for SCD in childhood HCM may provide individualized estimates of risk at 5 years using readily obtained clinical risk factors. External validation studies are required to demonstrate the accuracy of this model's predictions in diverse patient populations.
Keywords: Cardiomyopathy, Hypertrophic; Humans; dítě; Child; Death, Sudden, Cardiac; Female; rizikové faktory; hypertrofická kardiomyopatie; lidé; Europe; náhlá srdeční smrt; Follow-Up Studies; ženské pohlaví; Male; Retrospective Studies; Adolescent; prognóza; incidence; Incidence; Prognosis; retrospektivní studie; Risk Assessment; míra přežití; mužské pohlaví; hodnocení rizik; Evropa; následné studie; mladiství; Risk Factors; Survival Rate